2014
DOI: 10.1074/jbc.m114.579714
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Pneumococcal Peptidoglycan Hydrolase LytB Reveals Insights into the Bacterial Cell Wall Remodeling and Pathogenesis

Abstract: Background:The pneumococcal endo-␤-N-acetylglucosaminidase LytB is required for cell division and colonization. Results: Structural analysis revealed that the catalytic domain of LytB consists of three structurally distinct modules. Conclusion: All three modules of LytB are necessary for its optimal activity toward peptidoglycan hydrolysis and for pneumococcal adhesion to respiratory epithelial cells. Significance: Provided is the structural insight into LytB-mediated pneumococcal cell wall remodeling and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 62 publications
5
64
0
Order By: Relevance
“…The N ‐acetylglucosaminidase LytB (SPD_0853; p I of the mature protein 5.0), which is responsible for daughter cell separation (De las Rivas et al ., ), is also involved in pneumococcal attachment to nasopharyngeal cells, and in adhesion to and invasion of lung epithelial cells (Ramos‐Sevillano et al ., ; Bai et al ., ). LytB is also required for optimal in vitro biofilm formation (Moscoso et al ., ), and the addition of up to 0.5 μg ml −1 of purified LytB boosted biofilm formation by a lytB pneumococcal mutant (Domenech et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N ‐acetylglucosaminidase LytB (SPD_0853; p I of the mature protein 5.0), which is responsible for daughter cell separation (De las Rivas et al ., ), is also involved in pneumococcal attachment to nasopharyngeal cells, and in adhesion to and invasion of lung epithelial cells (Ramos‐Sevillano et al ., ; Bai et al ., ). LytB is also required for optimal in vitro biofilm formation (Moscoso et al ., ), and the addition of up to 0.5 μg ml −1 of purified LytB boosted biofilm formation by a lytB pneumococcal mutant (Domenech et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…PK, the binding mixture was digested with proteinase K (100 μg ml −1 ; 15 min, 37°C) after allowing the formation of the CbpF−DNA complex. (Ramos-Sevillano et al, 2011;Bai et al, 2014). LytB is also required for optimal in vitro biofilm formation (Moscoso et al, 2006), and the addition of up to 0.5 μg ml −1 of purified LytB boosted biofilm formation by a lytB pneumococcal mutant (Domenech et al, 2013a).…”
Section: Optimal Conditions For Cbp-dna Complex Formation In Vitromentioning
confidence: 99%
“…AcpCD has a deep substrate‐binding groove constructed by three subdomains, the central subdomain, a relatively large arm subdomain, and an additional subdomain, giving a unique structure to AcpCD among GH73 family enzymes (Fig. S3) . Although the zymography analysis demonstrated that AcpCD does not exhibit species specificity, this structural feature of AcpCD may be favorable to hydrolyze the peptidoglycan of C. perfringens .…”
Section: Discussionmentioning
confidence: 99%
“…All share an ␣/␤-hydrolase-fold with a deep cleft that accommodates their glycan substrates and a conserved active site. With each, the identities of the catalytic acid/base residues is clear and they (21,49,50), together with the homolog of Staphylococcus warneri Atl (51), have been proven experimentally. These findings were confirmed in the current study with the significant decrease in catalytic activity found with S. typhimurium (Glu 184 3 Gln)FlgJ C .…”
Section: Discussionmentioning
confidence: 99%